Bulk Heterojunction Organic Solar Cell Area-Dependent Parameter Fluctuation - A. J. Trindade; L. Pereira (International Journal of Photoenergy)
Organic solar cell efficiency is known to be active area dependent and is usually a problem in the upscale factor for market applications. In this work, a detailed study of organic photovoltaic devices with active layer based on poly(3-hexylthiophene) (P3HT) and 1-(3-methoxycarbonyl)-propyl-1-phenyl-(6,6)C61 (PCBM) is made, evaluating the effect of the change on the active area from 10−2 to 4 cm4. The device structure was kept simple in order to allow the understanding of the physical effects involved. Device figures of merit were extracted from the equivalent circuit using a genetic-based algorithm, and their relationship with the active area was compared. It is observed that the efficiency drops significantly with the active area increase (as the fill factor) while the parallel and series resistance, adjusted to the active area, seems to be relatively constant and increases linearly, respectively. The short circuit current and the generated photocurrent also drop significantly with the active area increase. The open circuit voltage does not show major changes. These results are discussed considering the main influences for the observed efficiency data. Particularly, as the basic circuit model seems to fail to explain the macroscopic results, the behavior can be related with the enlargement of defect interaction.